Hypo-Albuminemia and Perioperative Renal Transplant-Related Infections: A Systematic Review and Meta-Analysis - Mohammadi, Abdolreza; Inanloo, Seyed Hassan; Rezaeian, AhmadReza; Menbari Oskouie, Iman; Khajavi, Alireza; Mirzaei, Akram; Ahmadi Pishkuhi, Mahin; Oliveira Reis, Leonardo; Aghamir, Seyed Mohammad Kazem (Urology Journal, 2024)
Objective: to review the literature regarding the relationship between pre- and post-transplant hypo-Albuminemia with various renal transplant-related infections. Materials and Methods: In a systematic review, we included the following keywords in the search: (Albumin*) AND (infection*) AND ("renal transplant" OR "renal transplantation" OR "renal transplants") OR ("kidney transplant" OR "kidney transplantation" OR "kidney transplants") OR "kidney grafting") with investigating databases including ProQuest, PubMed, Scopus, and Web of Science to May 2023. All adult patients who had renal transplantation were included. Albumin levels of infected (bacterial, fungal, or viral) patients and the type of infection should be reported in the included studies. The search strategy used in this review was reported by Preferred Reporting Items for Systematic Reviews and Meta-Analyses literature search extension (PRISMA-S). To conduct Meta-analyses, Stata version 17 was used. Also, DerSimonian-Laird random-effects models were used for this study. In our study, heterogeneity was quantified with I2 and τ2 statistics. Inconsistency across studies is quantified by I2 statistics, and the impact of heterogeneity on the meta-analysis is assessed by this quantification. Results: Overall, 18 studies were found to be reporting measures of association including risk ratio, odds ratio, and, hazard ratio. Among them, 10 and 8 studies reported bacterial and viral types of infection. The combined risk ratios were not statistically significant, in either type of infection. The mean (SD) of ages for bacterial and viral infections were found to be 45.3 (6.4) and 50.5 (7.6) years old, respectively. Conclusion: Hypoalbuminemia is not related to post-transplantation infections, and it seems that with adherence to proper pretransplant screening of recipients, vaccination, and post-transplant surveillance and prophylaxis, the impact of infections may be reduced.